La historieta: elementos y estructura - Saavedra Salazar, Marlon René (2021)
The purpose of this Professional Sufficiency Work entitled "The comic strip: elements and structure" is to support a learning session for second grade high school students, where students will understand the meaning of the comic strip, its characteristics, structure and elements it contains, as well as its purpose and usefulness for society. The comprehension of texts is a useful competence for the intellectual development of the student, facing this need arises the involvement of an adequate teaching for such learning. The usefulness of instructional texts allows this development and in turn the application of a learning session as the theme of the cartoon will allow introducing young people in the world of reading analysis; since this theme is appropriate because it is presented in a striking way, full of colors, symbologies and onomatopoeias; where the student can read without getting bored. Thus, this work proposes the main development of critical capacity, based on the analysis of reading, and it is also contextualized for the application in a virtual environment where all young people have access to the Internet and manage applications related to education.